Religious Moderation on Food and Environmental Balance: Local Practices of Muslims and Confucians in Pontianak, West Kalimantan - Hidayat, Samsul; Haiming, Wen; Cukarestu, Yesica; Setiawan, Chandra (LP2M - Universitas Islam Negeri Walisongo Semarang, 2024)
The study on the role of religious moderation in food consumption practices as a strategy to maintain environmental balance highlights the unique synergy between Islamic and Confucian values within the local context of Pontianak, West Kalimantan, Indonesia. This article explores the moderate practices of Muslims and Confucians in Pontianak in valuing food to maintain environmental balance. More specifically, this article asks how Islamic and Confucian values of moderation are reflected and integrated into daily consumption practices to maintain environmental balance sustainably. Data was collected through in-depth interviews with informants representing Muslim and Confucian communities. The results show that both communities own environmentally friendly practices reflected in efforts to reduce food waste and control consumption. The concept of moderation and balance in Islam and Confucianism is the main foundation of this practice, as well as religious teachings, cultural norms, and ethical values. The findings suggest that environmental stewardship can be a point of convergence between religion and culture to maintain the sustainability of natural resources. These findings’ policy and conceptual implications can be used to promote awareness of environmental stewardship among Muslim and Confucian communities and develop inclusive sustainability strategies. Further studies can expand the scope and go deeper in understanding sustainable behavior in diverse cultural contexts.